(untitled) (Journal of Asian Development Studies, 2016)
This paper shows why it is that in Economics text books and literature we invariably consider constant returns to scale (linearly homogeneous production functions) and not increasing returns to scale or decreasing returns to scale production . It has been demonstrated in this paper by using both cost elasticity output approach and Euler’s theorem that the constant returns to scale production functions enable us to achieve productive efficiency and equilibrium. Production under increasing returns to scale or decreasing returns to scale are not at equilibrium. Only under constant returns to scale technology do we achieve productive efficiency and equilibrium.